2012
DOI: 10.1177/0266666911431740
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic mechanisms for promoting ICT investment and use in cassava value chains in south-western Nigeria

Abstract: The transformation of African agriculture with modern technologies, including information and communication technology (ICT) has been proposed as the required strategy for improving agricultural and rural economies of African countries. In this direction, this study investigated the catalysts and impact of ICT investment, ownership and use in the cassava value chain in south-western Nigeria. The study used in-depth structured interviews to collect data from 139 cassava growers, processors and marketers. Snowba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Similarly, Tiamiyu 10 examined the factors underlying the use of information sources in government institutions. The study revealed that certain characteristics of information sources can be used to explain their use or non-use.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tiamiyu 10 examined the factors underlying the use of information sources in government institutions. The study revealed that certain characteristics of information sources can be used to explain their use or non-use.…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, algunos estudios de firmas manufactureras han encontrado una relación negativa entre las variables relacionadas con las tecnologías de la información y el desempeño de las empresas (Tiamiyu et al, 2012).…”
Section: Efecto De Las Tic Sobre El Desempeñounclassified
“…De acuerdo con lo hallado en la literatura (Chege & Wang, 2020;Edgar Gálvez et al, 2014;Gonzálvez-Gallego et al, 2015;Menéndez et al, 2007;Morera Chacon, 2014;Tiamiyu et al, 2012), y lo propuesto principalmente por Peñates (2014) es posible hablar de efectos del uso de las TIC sobre el desempeño organizacional, del tipo 1) positivo-significativo, 2) neutro (no significativo), o 3) negativo. Adicionalmente, dichos impactos pueden ser de forma 1) directa, 2) indirecta, y 3) co-directa (Peñates, 2014) Por otro lado, además de las variables que permitirán cuantificar las diferentes dimensiones del desempeño organizacional, diversos estudios proponen la inclusión de otras variables que faciliten controlar la heterogeneidad al interior de los modelos de estudio (Edgar Gálvez et al, 2014;Gonzálvez-Gallego et al, 2015;Hejazi, Ghanbari, & Alipour, 2016;Maldonado Guzmán et al, 2010;Powell & Dent-Micallef, 1997;Wong et al, 2009).…”
Section: Efecto De Las Tic Sobre El Desempeñounclassified
“…In (Asenso-Okyere & Mekonnen, 2012) argues that the national objectives of achieving universal and affordable access to the full range of communications services in most African countries have been undermined either by poor policies constraining market entry and the competitive allocation of available resources; weak institutional arrangements with a death of technical capacity and competencies; and, in some instances, regressive taxes on usage. It is observed in (Tiamiyu, et al, 2012) that one of the key factors affecting use of ICT in agriculture is inappropriate ICT policies, especially those targeting rural communities and rural development, language barriers, poor information sharing culture, and the fact that not all people in rural areas have even the low-end ICT such as radio and television. Although there have been various attempts to introduce ICT to small-scale farmers in Africa to provide effective communication and information services, these efforts have been mostly through uncoordinated projects.…”
Section: Challenges In Ict Adoption By Farmers To Support Agriculturementioning
confidence: 99%
“…Most farming activities in Africa are on small scale (Lotter, 2007) and the problems of these farmers are multifaceted including (Munyua & Adera, 2009;Tiamiyu, Bankole, & Agbonlahor, 2012): sub-divisions and small farm sizes, leading to diseconomies of scale and low productivity; inadequate knowledge and skills in modern farming techniques and optimum methods of management; storage difficulties and inadequate farmer experience with the marketing of produce; poor linkages between farmers, processors, markets, researchers and extension workers. (Munyua & Adera, 2009) also notes that African farmers often lack adequate information on inputs, markets, credit, improved technologies, commercial farming and other aspects of rural development, and that the use of ICT to deliver training and information is a critical ingredient for improving access to markets, production and productivity.…”
Section: Introductionmentioning
confidence: 99%